(3x-2y)2= solve?

3x-2y2

#1

(3x-2y)2=?

Answer:

This problem uses the Distributive Property of Multiplication. It states that when you add or subtract a bunch of numbers and then multiply THAT result by another number, you get the same answer as FIRST multiplying each of the numbers by the multiplier and THEN doing all of the adding and subtracting.

In other words (using generic variables): (A+B-C)X = (AX) + (BX) - (CX)

So in this case, (3x - 2y)2 = (3x2) - (2y*2) = (6x) - (4y) . At this point we can’t simplify any more because the variables are different types. So this is our final answer: 6x - 4y.